PENERAPAN MODEL PEMBELAJARAN MISSOURI MATHEMATICS PROJECT DAN TEAMS GAMES TOURNAMENT UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH - Yasinta Sugiah (UJMES (Uninus Journal of Mathematics Education and Science), 2020)
The background of this research is the low matematical problem solving ability of students. To improve students' mathematical problem solving abilities the application of the missouri mathematics project (MMP) and team games tournament (TGT) learning models is used. The research aims to find out the improvement of students 'mathematical problem solving abilities through the application of a combination of MMP learning models and TGT is better than the problem based learning (PBL) learning model and students' responses to the application of the MMP learning model mix and the TGT. The method used in this research is quasi-experimental. The population in this study were all grade VII students of SMP Negeri 1 Bojongsoang. The sample is students of class VII-D as an experimental class given a combination of MMP learning models and TGT and class VII-E as a control class given a PBL model. The instruments used were tests of mathematical problem solving abilities, student questionnaires, and observation sheets. Based on the analysis of the mathematical problem solving ability test results, it was concluded that the improvement of students' mathematical problem solving abilities through the application of a MMP learning model and TGT was better than the PBL model and based on the questionnaire analysis, it was concluded that the students responded positive towards the application of the MMP learning model mix and the TGT.